Analisis Kemampuan Berpikir Kreatif Matematis Berdasarkan Kepercayaan Diri Siswa Kelas VIII SMP Negeri 4 Tambang Pada Materi Sistem Persamaan Linier Dua Variabel (SPLDV) (Tarbiyah Suska Conference Series, 2022)
This study aims to analyze and describe mathematical creative thinking skills based on the self-confidence of class VIII students of SMP Negeri 4 Tambang on the material of a two-variable linear equation system. This type of research is descriptive qualitative research. The subjects in this study were 9 grade VIII students of SMP Negeri 4 Tambang who were selected using purposive sampling technique. Data were collected using questionnaires, tests and direct interviews. The instrument used is a self-confidence questionnaire, a test of mathematical creative thinking skills as many as 4 questions in the form of descriptions and interview guidelines. All data were then analyzed through 3 stages, namely data reduction, data presentation and conclusion drawing. The results of the research and data analysis concluded that the self-confidence of grade VIII students of SMP Negeri 4 Tambang was different. Overall students' mathematical creative thinking skills are in the very poor category with a percentage of 51.3%. Students with a high level of self-confidence have very good mathematical creative thinking skills. Students with moderate level of self-confidence have sufficient.